2021
DOI: 10.12998/wjcc.v9.i28.8579
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole therapy for infant hemangioma: Two case reports

Abstract: BACKGROUND Infantile hemangiomas (IHs) are the most common childhood benign tumors, showing distinctive progression characteristics and outcomes. Due to the high demand for aesthetics among parents of IH babies, early intervention is critical in some cases. β-Adrenergic blockers and corticosteroids are first-line medications for IHs, while itraconazole, an antifungal medicine, has shown positive results in recent years. CASE SUMMARY In the present study, itraconazole wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Itraconazole prevented lung cancer endothelial cells from proliferating and migrating; moreover, it exhibited an antiangiogenic effect via the inhibition of tube formation [ 16 ]. Itraconazole has been proven to be a potential therapeutic for IH in various studies [ 6 , 7 , 11 , 17 ]. Another study reported that itraconazole promoted the regression of IH through the inhibition of platelet-derived growth factor (PDGF) [ 18 ]; however, this finding can only partly explain the inhibitory effect of itraconazole on IH.…”
Section: Discussionmentioning
confidence: 99%
“…Itraconazole prevented lung cancer endothelial cells from proliferating and migrating; moreover, it exhibited an antiangiogenic effect via the inhibition of tube formation [ 16 ]. Itraconazole has been proven to be a potential therapeutic for IH in various studies [ 6 , 7 , 11 , 17 ]. Another study reported that itraconazole promoted the regression of IH through the inhibition of platelet-derived growth factor (PDGF) [ 18 ]; however, this finding can only partly explain the inhibitory effect of itraconazole on IH.…”
Section: Discussionmentioning
confidence: 99%